Effects of trunk training using motor imagery on trunk control ability and balance function in patients with stroke - Yan-fang Sui; Zhen-hua Cui; Zhen-hua Song; Qian-qian Fan; Xia-fei Lin; Binbin Li; Lang-qian Tong (BMC, 2023)
Abstract Objective To explore the effects of trunk training using motor imagery on trunk control and balance function in patients with stroke. Methods One hundred eligible stroke patients were randomly divided into a control group and trial group. The control group was given routine rehabilitation therapy, while the trial group was given routine rehabilitation therapy and trunk training using motor imagery. Results Prior to treatment, there was no significant difference between the two groups (P > 0.05) in Sheikh's trunk control ability, Berg rating scale (BBS), Fugl-Meyer assessment (FMA), movement length, movement area, average front-rear movement speed, average left-right movement speed, and surface electromyography (sEMG) signal of the bilateral erector spinae and rectus abdominis. After treatment, Sheikh's trunk control ability, FMA, and BBS in the two groups were significantly higher than those before treatment (P < 0.05). The movement length, movement area, the average front-rear movement speed, and the average left-right movement speed in the two groups decreased significantly (P < 0.05). The differences of these indicators between the two groups were statistically significant (P < 0.05). After treatment, the rectus abdominis and erector spinae on the affected side of the two groups improved when compared with those before treatment (P < 0.05). The rectus abdominis and erector spinae on the healthy side of the trial group descended after treatment (P < 0.05), while little changes were observed on the healthy side of the control group after treatment (P > 0.05). The rectus abdominis and erector spinae on the affected side of the trial group improved when compared with those in the control group (P < 0.05). There was no significant difference between the two groups in the decline of abdominalis rectus and erector spinal muscle on the healthy side. Conclusion Trunk training using motor imagery can significantly improve the trunk control ability and balance function of stroke patients and is conducive to promoting the recovery of motor function.